Kebijakan Negara dalam Mengakomodir Agama Pribumi Perspektif Sosial-Antropologi - Aziz Faiz, Abd (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2018)
Indonesia as a multicultur state has accommodating and acknowledged the existence of indigenous religions with other names, Penghayat Kepercayaan (belivers of mystical gorup), even its position now equivalent to six religions recognized by the state, but in the context of practical services it needs to be investigated further. Unfortunately, the state has not used the definition of religion social-anthropologically yet, it uses a biased politically definition. The implication is that the state see indigenous religion as not religion. This led to the need for religiousization of it followers which led to the conflicts of mission from six world religions. Because of this, indigenous religions experienced conflict with the state, in the same time it also conflict with six world religions. Their position was finally squashed, therefore the recommendations of this paper looked at the need for Penghayat Kepercayaan to be placed in the Ministry of Religion by forming the BIMAS Penghayat Kepercayaan, at least the country put indigenous religion important and equivalent with six world religions.Indonesia sebagai negara multikultur telah mengakomodir dan mengakui eksistensi agama pribumi dengan nama lain yaitu Penghayat Kepercayaan, dan bahkan kedudukannya setara dengan agama besar, meski dalam konteks pelayanan praktis perlu diteliti lebih jauh. Sayangnya hinga saat ini negara belum menggunakan definisi agama secara sosial-antropologis, tetapi menggunakan definisi yang bias politik kekuasaan. Implikasinya adalah negara memandang agama pribumi bukan agama. Hal ini membawa perlunya agamaisasi pengikut agama pribumi yang menimbulkan konflik misi dari agamaagama besar. Karena itu, agama pribumi mengalami konflik dengan negara, juga dengan agama-agama besar sekaligus. Posisi mereka akhirnya serba terjepit, karena itu rekomendasi tulisan ini memandang perlu Penghayat Kepercayaan diletakkan di Kementerian Agama dengan membentuk BIMAS Penghayat Kepercayaan, setidaknya dengan demikian negara meletakkan agama pribumi penting dan setara dengan agama besar lainnya.